Paleotsunami Inundation of a Beach Ridge Plain: Cobble Ridge Overtopping and Interridge Valley Flooding in Seaside, Oregon, USA. (18th August 2010) - Peterson, Curt D.; Jol, Harry M.; Horning, Tom; Cruikshank, Kenneth M.
Abstract : The Seaside beach ridge plain was inundated by six paleotsunamis during the last ~2500 years. Large runups (adjusted >10 m in height) overtopped seawardmost cobble beach ridges (7 m elevation) at ~1.3 and ~2.6 ka before present. Smaller paleotsunami (6–8 m in height) likely entered the beach plain interior (4-5 m elevation) through the paleo-Necanicum bay mouth. The AD 1700 Cascadia paleotsunami had a modest runup (6-7 m height), yet it locally inundated to 1.5 km landward distance. Bed shear stresses (100–3, 300 dynec m − 2 ) are estimated for paleotsunami surges (0.5–2 m depths) that flowed down slopes (0.002–0.017 gradient) on the landward side of the cobble beach ridges. Critical entrainment shear stresses of 1, 130–1, 260 dynec m − 2 were needed to dislodge the largest clasts (26–32 cm diameter) in paleotsunami coulees that were cut (100–200 m width) into the landward side of the cobble ridges.